POLA KEMATIAN DAN INTENSITAS SERANGAN PARASIT PADA IKAN LELE YANG DIBUDIDAYAKAN DENGAN DUA SISTEM YANG BERBEDA - Angga Kartika, Gde Raka; Amelia, Novita; Angga Pebriani, Dewa Ayu (University of Prof. Dr. Hazairin, SH, 2023)
This study aimed determine the parasite infection intensity value and mortality pattern of catfish (Clarias gariepinus) cultivation with different systems. The cultivation system used is intensive and intensive + bio floc system. The research design used is CRD (Complete Randomized Design), using two treatments with three repetitions. The research activities included sampling, ectoparasite examination, identification, and water quality examination. The total samples studied in this research were 24 fish in each treatment. Fish parts observed were the body surface, gills, and fins. The results of the research conducted show that, at the beginning to the end of the study, the mortality rate of fish has decreased. Then, the highest parasite infection intensity value was found in the intensive treatment, with a moderate infection category.